A study to determine the effect of maternal prepregnancy body mass index on the anthropometric measurements of the newborn - Kumar, Brinda Prasanna; Adarsh, E.; G., Sahana (International Journal of Contemporary Pediatrics, 2020)
Background: Maternal pre-pregnancy BMI is well established to be a detrimental factor for prenatal development and neonatal anthropometric measures. Objectives of the study was to study the association between maternal pre-pregnancy Body Mass Index (BMI) and the anthropometry of the newborn. Methods: A hospital based cross-sectional, observational study was conducted that included 236 normal newborns and their mothers. A pre-designed questionnaire was used to collect relevant socio-demographic data and obstetric history. Details regarding maternal pre-pregnancy weight was collected from antenatal records at first antenatal visit, maternal height was measured and BMI was calculated. Neonatal anthropometric measurements including birth weight, recumbent length, head circumference, chest circumference and the mid arm circumference was measured. Results: In this study 49.6% of the women were in the age group of 21-25 years, 52.5% of them were multi-gravida and 56.4% had normal vaginal delivery. Among the newborns included in the study 25.8% had low birth weight. We saw a significant positive correlation between BMI and age, BMI and birth weight, BMI and chest circumference that is with increase in BMI there was significant increase in the age, birth weight and chest circumference and vice versa. There was no association between maternal BMI and mid-arm circumference or head circumference of the newborn. Conclusions: Study showed the association between maternal BMI and anthropometry of the newborn especially with respect to the BMI and birth weight, BMI and chest circumference. Thereby, establishing that interventions aimed at improving the nutritional status of the mother have a direct impact on the fetal growth outcomes.